Early conversion of classic Fontan conversion may decrease term morbidity: single centre outcomes. (28th August 2019) - Blitzer, David; Habib, Asma S.; Brown, John W.; Kean, Adam C.; Lin, Jiuann-Huey I.; Turrentine, Mark W.; Rodefeld, Mark D.; Herrmann, Jeremy L.; Kay, William Aaron
Abstract: Background: The initial classic Fontan utilising a direct right atrial appendage to pulmonary artery anastomosis led to numerous complications. Adults with such complications may benefit from conversion to a total cavo-pulmonary connection, the current standard palliation for children with univentricular hearts. Methods: A single institution, retrospective chart review was conducted for all Fontan conversion procedures performed from July, 1999 through January, 2017. Variables analysed included age, sex, reason for Fontan conversion, age at Fontan conversion, and early mortality or heart transplant within 1 year after Fontan conversion. Results: A total of 41 Fontan conversion patients were identified. Average age at Fontan conversion was 24.5 ± 9.2 years. Dominant left ventricular physiology was present in 37/41 (90.2%) patients. Right-sided heart failure occurred in 39/41 (95.1%) patients and right atrial dilation was present in 33/41 (80.5%) patients. The most common causes for Fontan conversion included atrial arrhythmia in 37/41 (90.2%), NYHA class II HF or greater in 31/41 (75.6%), ventricular dysfunction in 23/41 (56.1%), and cirrhosis or fibrosis in 7/41 (17.1%) patients. Median post-surgical follow-up was 6.2 ± 4.9 years. Survival rates at 30 days, 1 year, and greater than 1-year post-Fontan conversion were 95.1, 92.7, and 87.8%, respectively. Two patients underwent heart transplant: the first within 1 year of Fontan conversion for heart failure and the second at 5.3 years for liver failure. Conclusions: Fontan conversion should be considered early when atrial arrhythmias become common rather than waiting for severe heart failure to ensue, and Fontan conversion can be accomplished with an acceptable risk profile.